Advanced glycation end-products disrupt human endothelial cells redox homeostasis: new insights into reactive oxygen species production. (1st February 2019) - Dobi, Anthony; Bravo, Susana B.; Veeren, Bryan; Paradela-Dobarro, Beatriz; Álvarez, Ezequiel; Meilhac, Olivier; Viranaicken, Wildriss; Baret, Pascal; Devin, Anne; Rondeau, Philippe
Abstract: Advanced glycation end-products (AGEs) trigger multiple metabolic disorders in the vessel wall that may in turn lead to endothelial dysfunction. The molecular mechanisms by which AGEs generate these effects are not completely understood. Oxidative stress plays a key role in the development of deleterious effects that occur in endothelium during diabetes. Our main objectives were to further understand how AGEs contribute to reactive oxygen species (ROS) overproduction in endothelial cells and to evaluate the protective effect of an antioxidant plant extract. The human endothelial cell line EA.hy926 was treated with native or modified bovine serum albumin (respectively BSA and BSA-AGEs). To monitor free radicals formation, we used H2 DCF-DA, dihydroethidium (DHE), DAF-FM-DA and MitoSOX Red dyes. To investigate potential sources of ROS, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and mitochondrial inhibitors were used. The regulation of different types of ROS by the polyphenol-rich extract from the medicinal plant Doratoxylon apetalum was also studied for a therapeutic perspective. BSA-AGEs exhibited not only less antioxidant properties than BSA, but also pro-oxidant effects. The degree of albumin glycoxidation directly influenced oxidative stress through a possible communication between NADPH oxidase and mitochondria. D. apetalum significantly decreased intracellular hydrogen peroxide and superoxide anions mainly detected by H2 DCF-DA and DHE respectively. Our results suggest that BSA-AGEs promote a marked oxidative stress mediated at least by NADPH oxidase and mitochondria. D. apetalum plant extract appeared to be an effective antioxidant compound to protect endothelial cells.